Damage effects of double-spaced aluminum plates by reactive material projectile impact. (June 2017) - Xu, F.Y.; Yu, Q.B.; Zheng, Y.F.; Lei, M.A.; Wang, H.F.
Highlights: The maximum damage sizes on rear plate are 66.3 times of sectional area of the projectile. Damage sizes of rear plate show an increase with increasing of impact velocity or decreasing of front plate thickness. Plugging damage to the front plate is caused by the kinetic energy impact of reactive projectile. Damage to the rear plate is caused by the kinetic energy impact of residual projectile and fragment cloud. The chemical energy release of reactive materials may enhance damage to the rear plate. Abstract: Damage effects of the double-spaced aluminum plates, impacted by the cold isostatically pressed and sintered PTFE/Al/W reactive material projectile with a density of 7.8 g/cm 3, were investigated by the ballistic impact experiments and the theoretical analyses. Three kinds of the double-spaced plates with the thicknesses of 3 mm/3 mm, 6 mm/3 mm and 6 mm/6 mm were used. The distance between the front and the rear plate was 200 mm. The cylindrical reactive projectile with the mass of 8 g was launched at the velocities of approximate 710 m/s∼950 m/s to impact the target. It has been shown that the plugging damage pattern is formed on the front plate impacted by the reactive projectile. Moreover, damage to the rear plate is significantly influenced by the impact velocity and the front/ rear plate thickness. For mechanism consideration, the plugging damage to the front plate is caused by the kinetic energy impact of the reactive projectile. However, damage to the rear plate is caused by the kinetic energy impact of residual projectile and fragment cloud. The chemical release may also enhance the damage to the rear plate.